Endovascular treatment for acute pulmonary embolism in neurological patient - Gunchan, Paul; S, Paul Birinder; L, Gautam Parshotam; Bishav, Mohan; Shruti, Sharma (International Journal of Health Sciences, 2015)
Among the spectrum of venous thrombo-embolic disease, acute pulmonary embolism accounts for the most life threatening manifestations with mortality exceeding 50%. It can affect many patient populations across various disciplines, hence immediate attention and aggressive treatment is crucial. With the advancement of technologies, various catheter-based devices are available to treat massive or submassive PE. In this paper we report two patients of acute pulmonary embolism with neurological issues where the life threatening emergency was successfully managed by utilizing endovascular directed thrombolytic reperfusion therapy. Â